Scooby-Doo! : the pizza place ghost - Duendes Del Sur (Firm); Cartoon Network (Television network); Class 1-208. (New York : Scholastic Inc., 2000)
Scooby-Doo and the gang find out if the pizza place is really haunted.
"A little apple paperback."
At head of title: Cartoon Network.
"Preschool-Grade 1"--Back cover.
NP
Keywords: Dogs -- Juvenile fiction; Ghost stories; Restaurants -- Juvenile fiction; Dogs -- Fiction; Ghosts -- Fiction; Restaurants -- Fiction; Mystery fiction